Sports and dreaming: an online survey of American adults - Bulkeley, Kelly; Schredl, Michael (Dreaming, 2023)
The results of an online survey of 4,588 demographically diverse American adults provide insight into the questions of (a) who in the general population tends to have sports-related dreams, (b) how does interest in sports relate to dreaming about sports, and (c) what are the typical themes in sports-related dreams? A quantitative and qualitative analysis of the participants’ responses indicates that sports dreams occur among a wide range of people, especially among men, people with higher education, people who are interested in sports, and people with high dream recall. Sports-related dreams correlate more strongly with waking-life interest in sports than waking-life participation in sports. The sports that appeared most frequently in dreams were basketball, football, baseball, soccer, running, swimming, and golf. The contents of sports-related dreams tended to include more winning than losing, more unusual alterations than realistic portrayals of sports scenarios, and more active playing rather than passive watching. (PsycInfo Database Record (c) 2023 APA, all rights reserved)